Pengaruh Penerapan Model Pembelajaran Sains Teknologi Masyarakat (STM) Terhadap Kemampuan Literasi Sains Siswa Pada Materi Larutan Elektrolit dan Non Elektrolit - Noprima Lika (Journal of Research and Education Chemistry, 2021)
Science literacy was the capacity to use scientific knowledge, to identify questions, to draw a conclusion based on the facts, evidence, and data in order to understand and help researchers to make decisions about the natural world and human interactions with the nature. This research aimed at knowing the effect of implementing Science, Technology, and Society (STS) learning model toward student science literacy ability on Electrolyte and non-Electrolyte Solution lesson at State Senior High School 2 Tambang. It was a quasi-experimental research with non-equivalent control group design. Purposive sampling technique was used in this research. The data were obtained from test and interview. The research findings showed that the score of Sig. (2-tailed) 0.000 was smaller than 0.05 (0.000<0.05), and tobserved was higher than ttable (11.564>1.667). Based on the basis for decision making in Independent Sample t- test, it could be concluded that Ha was accepted and H0 was rejected. It meant that there was an effect of implementing STS learning model toward student science literacy ability on Electrolyte and non- Electrolyte Solution lesson at State Senior High School 2 Tambang with the coefficient of effect 18.2%.